Testing the Moderating Role of Risk Preference in Enhancing the Intention to Implement Value-Added Tax Refund in Advance - Siharini, Dwi; Sofyani, Hafiez (Journal of Accounting and Investment, 2025)
Abstract Research aims: This research is motivated by the limited studies on Value Added Tax (VAT) restitution, particularly restitution with advance refunds. Therefore, this study aims to examine the influence of the variables of convenience, efficiency, and risk preference on the intention to implement restitution with advance refunds and taxpayer compliance. Design/Methodology/Approach: This research was conducted using a quantitative approach with an associative study design. The data used are primary data obtained from the distribution of questionnaires to respondents consisting of taxpayers in the Yogyakarta area. The research instrument used a set of five Likert scales. The present study also utilized Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. Research findings: This study shows that ease of use and efficiency positively influence the intention of corporate taxpayers to carry out VAT restitution with advance refunds, while risk preference does not have a significant impact.Risk preference has a positive but insignificant moderating effect on the intention to implement restitution with an advance refund and an insignificant negative effect in moderating the relationship between the influence of efficiency and the taxpayer's intention to apply for restitution. Theoretical contribution/Originality: This study provides insights into the factors influencing taxpayers' interest in restitution with advance refunds, such as ease, efficiency, and risk preference. Its findings can help improve tax refund services, inform policy development, and contribute to the academic literature on taxpayer behavior. Practitioner/Policy implication: This study highlights the need for the government and Yogyakarta Tax Office to simplify restitution procedures, speed up tax refund processes, and ensure transparency to reduce taxpayer concerns. It also stresses the importance of improving taxpayer education to encourage participation and suggests that responsive policies can enhance compliance and trust in the tax system. Research limitation/Implication: This research is limited to the taxpayer population located in the Yogyakarta region. Conditions and demographics in other regions may differ, so this research may not yet be able to depict the situation in those areas.